IMPLEMENTASI PRINSIP KEBEBASAN BERAGAMA DAN BERKEYAKINAN DI INDONESIA (Studi Kasus: Tanggung Jawab Negara dalam Konflik Sampang, Madura) - Rizky Adi Pinandito (Jurnal Pembaharuan Hukum, 2017)
The purpose of this study is to explain in depth how the responsibility of the state c.q Government of Indonesia against violations of the principle of freedom of religion in the case of Sampang, Madura. The method of approach used in this research is normative juridical in discussing the issue of implementation of protection and guarantee to freedom of religionand belief which is regulated in constitution and Indonesian legislation system and how state responsibility to religious conflict happened in Sampang, Madura, Jawa East. The results of the research conducted in the case of Sampang are, the security forces do not act or do omission(omission) in the event of riots. In addition, the government’s attitude that provoked provocation was shown by the MUI who issued a decree stating that the Shia taught by Tajul Muluk is heretical. The State should (in this case the Police) take precautions. Therefore, the State c.q The Government of Indonesia is obliged to provide compensation, restitution and rehabilitation to victims of human rights violations as well as to give legal assertiveness to all perpetrators of riots including government officials who allow the riots of human rights violations